2006
DOI: 10.1002/hep.21424
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute idiosyncratic drug-induced liver injury: Long-term follow-up in a hepatotoxicity registry

Abstract: A chronic adverse reaction may occur in some instances of drug-induced liver injury (DILI), even despite drug cessation. In our study, we obtained records from a Spanish registry and evaluated cases of DILI with biochemical evidence of long-term damage. Chronic outcome was defined as a persistent biochemical abnormality of hepatocellular pattern of damage more than 3 months after drug withdrawal or more than 6 months after cholestatic/mixed damage. Data on 28 patients with a chronic clinical evolution (mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
3
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(270 citation statements)
references
References 19 publications
(18 reference statements)
14
238
3
7
Order By: Relevance
“…In the Spanish Registry study acute cholestatic/mixed patterns had a greater tendency toward chronicity when compared to the hepatocellular type (9 vs. 4%, respectively; p < 0.031) (27), although residual lesion severity was greater in the latter (30% of cirrhosis and 20% of chronic hepatitis). Cardiovascular and CNS drug classes are more prone to chronic hepatotoxicity induction (27).…”
Section: Case Definition Phenotypes and Prognostic Determinantsmentioning
confidence: 90%
See 2 more Smart Citations
“…In the Spanish Registry study acute cholestatic/mixed patterns had a greater tendency toward chronicity when compared to the hepatocellular type (9 vs. 4%, respectively; p < 0.031) (27), although residual lesion severity was greater in the latter (30% of cirrhosis and 20% of chronic hepatitis). Cardiovascular and CNS drug classes are more prone to chronic hepatotoxicity induction (27).…”
Section: Case Definition Phenotypes and Prognostic Determinantsmentioning
confidence: 90%
“…In the Spanish Registry study acute cholestatic/mixed patterns had a greater tendency toward chronicity when compared to the hepatocellular type (9 vs. 4%, respectively; p < 0.031) (27), although residual lesion severity was greater in the latter (30% of cirrhosis and 20% of chronic hepatitis). Cardiovascular and CNS drug classes are more prone to chronic hepatotoxicity induction (27). Very recent analyses suggest that, regardless of the lesion's hepatocellular, cholestatic, or mixed pattern, most liver profile normalizations occur within one year, hence this cutoff could be most suitable to tell prolonged resolution from true chronic progression (28).…”
Section: Case Definition Phenotypes and Prognostic Determinantsmentioning
confidence: 90%
See 1 more Smart Citation
“…16 The poor prognostic implication of necrosis on biopsy have been appreciated in additional studies. 11,52 More formal analysis has additionally shown that the degree of necrosis, fibrosis stage, microvesicular steatosis, panacinar No specific associations Figure 7. Nodular regenerative hyperplasia due to a chemotherapeutic agent, showing compressed liver cell plates (arrows) alternating with a nodular area (asterisk) consisting of thickened plates (Gomori reticulin, original magnification 310).…”
Section: Prognostic Information On Liver Biopsymentioning
confidence: 99%
“…Merece destacarse asimismo que, aunque se realizó una biopsia hepática en un tercio de los pacientes de la serie, los hallazgos no fueron en general concluyentes para el diagnóstico de hepatotoxicidad, ya que el propio episodio de reexposición tenía un mayor peso. En circunstancias de reexposición la biopsia podría tener, pues, una utilidad principalmente de tipo pronósti-co. De hecho, en uno de estos episodios debido a bentazepam la biopsia fue consistente con una hepatitis cróni-ca activa, como ha sido previamente descrito con este fár-maco (21), y que incrementa el riesgo de persistencia de la lesión hepática (22,23). La indicación de la biopsia fue, en todo caso, más frecuente en la lesión hepatocelular, probablemente debido a que este tipo de lesión es más inespecífica, siendo más difícil su vinculación con la etiología tóxica (23).…”
Section: Discussionunclassified